2021
DOI: 10.1186/s41938-021-00396-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of some endophytic bacteria in biological control of root-knot nematode Meloidogyne incognita

Abstract: Background Root-knot nematodes (Meloidogyne spp.) are among the most important plant pathogens. Biological control is one of the safety and effective methods for control of these nematodes. The aim of the present study was the isolation and identification of endophytic bacteria from tomato fields in some areas of Iran in order to evaluate their biocontrol potential against root-knot nematode. In the present study, the population of Meloidogyne was collected from infected cucumber roots of a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…A. chroococcum, a nitrogen fixing bacteria and B. weidmannii NRC211 singly or combined in soil naturally infested with M. javanica recorded variable significant reductions in nematode developmental parameters with considerable increase in yield production and oil content. These data agree with previous studies on beneficial microorganisms in controlling plant pathogens and enhancing crop production (Moslehi et al 2021). The nematicidal activity of these bacterial agents might be due to secretion of antimicrobial compounds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A. chroococcum, a nitrogen fixing bacteria and B. weidmannii NRC211 singly or combined in soil naturally infested with M. javanica recorded variable significant reductions in nematode developmental parameters with considerable increase in yield production and oil content. These data agree with previous studies on beneficial microorganisms in controlling plant pathogens and enhancing crop production (Moslehi et al 2021). The nematicidal activity of these bacterial agents might be due to secretion of antimicrobial compounds.…”
Section: Discussionsupporting
confidence: 92%
“…This could be attributed to the fact that NPK contains a mixture of 4 microbial species viz: B. polymyxa, B. megaterium, B. circulance and Pseudomonas sp. Each one of these microbial strains has its own nematicidal mechanisms as well as its plant growth promoting effects as previously mentioned (Moslehi et al 2021). Moreover, A. chroococcum either single or combined with NPK treatments showed the greatest increase in number of pods, in addition NPK + Az combined treatment exhibited significant increase in pods weight, weight of 200 seeds, peanut crop production and oil content.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Several genera were predominant and determined the dissimilarities among the compartments (Figures S7-S10). Many of the biomarkers, including for Bacillus, Pseudomonas, Agrobacterium, Gemmatimonas, Enterobacter, Streptomyces, Devosia, Ensifer, Acinetobacter, Halomonas, Brevundimonas, Mesorhizobium, and Burkholderia, are known as beneficial microbes for plants, and these microbes may help to maintain plant hormone balance, control root development, facilitate nutrition acquisition, and prevent disease in the plant host [42,44,[51][52][53][54][55]. Several studies have reported that Streptomycetes are abundant inside of the roots of Arabidopsis thaliana [56] where they can have beneficial effects on growth [57] or protect plants against biotic and abiotic stressors [58,59].…”
Section: Root Compartment-specific Bacterial Biomarkers Varied With G...mentioning
confidence: 99%
“…The strain AzBw1 was introduced in an attempt to screen rhizobacteria based on their ability to control RKN of tomato plant (Moslehi et al 2021). This strain outperformed other strains such that in greenhouse conditions, root knots and egg mass development was considerably lower (60-70 percent) in AzBw1-treated plants in comparison to mock-treated plants.…”
Section: Introductionmentioning
confidence: 99%